Virtual dissections through micro‐CT scanning: a method for non‐destructive genitalia 'dissections' of valuable Lepidoptera material. (15th April 2014) - SIMONSEN, THOMAS J.; KITCHING, IAN J.
Abstract Since its first application to the field more than 10 years ago, micro‐computed tomography (micro‐CT) has been a state‐of‐the‐art technology in the study of insect morphology and anatomy. Despite showing great potential for various types of non‐destructive 'dissections', the method has, however, seen very limited use in descriptive taxonomy. Here we describe a method for carrying out virtual dissections of the genitalia in male Lepidoptera based on case studies involving the butterfly Argynnis paphia and the hawkmoth Cephonodes hylas. We demonstrate how a standard micro‐CT scanner in conjunction with freely available software can distinguish and illustrate taxonomically important characters, and propose a workflow by which valuable material (such as Linnaean types) can be made available as digital loans, and how users can subsequently carry out 'virtual dissections'. We emphasize that micro‐CT scanning does not remove the need for real dissections and morphological expertise to confidently evaluate virtual 'dissections'.